Myocardial Protection in Isolated Coronary Artery Bypass Grafting: Del Nido versus Blood Cardioplegia - Özkara,Taha (2022)
ABSTRACT Introduction: Our study aimed to examine the impacts of blood cardioplegia (BC) and del Nido cardioplegia (DNC) solutions - which we used in isolated coronary artery bypass grafting (CABG) - on early mortality and major adverse events (MAE). Methods: We retrospectively analyzed 329 consecutive patients who underwent CABG in our clinic between January 2016 and January 2020. Myocardial infarction, reoperation, cardiac tamponade, stroke, renal failure, extracorporeal membrane oxygenation requirement, and cardiopulmonary resuscitation were defined as MAE. The group in which DNC was used was Group D (181 [55%] patients), and the group in which BC was used was Group B (141 [45%] patients). Results: No statistically significant difference was determined between the groups regarding age, weight, body surface area, gender, or European System for Cardiac Operative Risk Evaluation score (P=0.615, P=0.560, P=0.934, P=0.365, P=0.955, respectively). Although there was no statistically significant difference between the groups in terms of aortic cross-clamping time (P=0.712), cardiopulmonary bypass duration was longer in Group B (P=0.001). Even though the incidence of stroke was higher in Group B (P=0.030), no statistically significant difference was observed between the groups regarding total incidence of MAE, mortality, mechanical ventilation time, length of stay in the intensive care unit, or length of hospital stay (P=0.153, P=0.130, P=0.689, P=0.710, P=0.613, respectively). Conclusion: We found no significant difference in MAE, mortality, duration of mechanical ventilation, intensive care unit stay, or hospital stay between the DNC and BC groups. We believe that both solutions can be used safely for cardiac protection in the adult patient population.